2013
DOI: 10.1186/cc11455
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced acute kidney injury and renal support for acute kidney injury: a KDIGO summary (Part 2)

Abstract: Acute kidney injury (AKI) is a common and serious problem affecting millions and causing death and disability for many. In 2012, Kidney Disease: Improving Global Outcomes completed the first ever international multidisciplinary clinical practice guideline for AKI. The guideline is based on evidence review and appraisal, and covers AKI definition, risk assessment, evaluation, prevention, and treatment. Two topics, contrast-induced AKI and management of renal replacement therapy, deserve special attention becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 115 publications
1
136
0
9
Order By: Relevance
“…However, avoidance of AKI by preventive measures remains the mainstay of management in high risk patients. Contrast induced AKI is probably an exception in that it is preventable and manageable by hydration, N-acetyl cysteine and bicarbonate [148] . Renoprotective measures include preventive simple maneuvers such as avoidance of nephrotoxic drugs, hydration, glycemic control, maintenance of renal perfusion and goal directed therapy (GDT), as well as more advanced pharmacological interventions [1,2,70,71] (Table 3).…”
Section: Prevention and Treatment On The Horizonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, avoidance of AKI by preventive measures remains the mainstay of management in high risk patients. Contrast induced AKI is probably an exception in that it is preventable and manageable by hydration, N-acetyl cysteine and bicarbonate [148] . Renoprotective measures include preventive simple maneuvers such as avoidance of nephrotoxic drugs, hydration, glycemic control, maintenance of renal perfusion and goal directed therapy (GDT), as well as more advanced pharmacological interventions [1,2,70,71] (Table 3).…”
Section: Prevention and Treatment On The Horizonmentioning
confidence: 99%
“…Most studies have found lower mortality with the earlier initiation of RRT [163,186,187] . In addition, recent guidelines suggest that using continuous RRT is superior to standard intermittent RRT in hemodynamically unstable patients [148] . It is clinically indicated and applicable, although reviews to date have not found differences in survival between the two modes [188] .…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Aunque hay diversos estudios publicados, con resultados dispares, basándose en la evidencia de los meta-análisis más recientes, que comparan la incidencia de NAC tras la administración de contraste iso-osmolar versus hipo-osmolar, el grupo KDIGO (Kidney Disease: Improving Global Outcomes) recomienda utilizar en pacientes con riesgo alto de desarrollar NAC, tanto el contraste iso como el hipo-osmolar, en contra del hiperosmolar (46) .…”
Section: Fisiopatología De La Nefropatía Asociada a Contrasteunclassified
“…Tabla 3. Estrategias evaluadas para disminuir el riesgo de NAC (28) En las guías KDIGO (46) se establece que el riesgo de NAC es clínicamente importante cuando la creatinina plasmática basal es ≥ 1,3 mg/dl en varones, y ≥ 1,0 mg/dl en mujeres, equivalente a un filtrado glomerular estimado de < 60 ml/minuto por 1.73 m 2 (82) . Aunque otros autores (83) mostraron que la incidencia de Insuficiencia renal aguda era significativa sólo cuando la concentración de creatinina basal era > 1.8 mg/dl, se recomienda realizar medidas preventivas cuando el FG estimado sea < 60 ml/min por 1.73 m 2 .…”
Section: Incidencia Factores De Riesgo Y Pronóstico De La Nacunclassified
See 1 more Smart Citation